Expiration of Commitment in Islamic Jurisprudence and the Civil Law of Afghanistan - Tafakury, Abdulmaroof (Integrated Journal for Research in Arts and Humanities, 2024)
Commitment in jurisprudence is a legal relationship between two persons, by virtue of which the liability of one is engaged in favor of the other. The legal system of Afghanistan, in Article 488 of its Civil Code, defines commitment as follows: "A personal right or obligation is a relationship between the creditor's and the debtor's conscience, by virtue of which the creditor can demand from the debtor the granting of a thing, the performance of an act or the abstention from it." The expiration of commitment is one of the major and specialized topics in the jurisprudence and civil law of Afghanistan. Commitment in jurisprudence is extinguished through fulfillment of the covenant, release, rescission or dismissal, impossibility of enforcing the commitment, unity of obligation, expiration of the term of commitment, set-off, assignment, death of the obligor and loss of capacity, and in the legal system of Afghanistan, it is extinguished through fulfillment of the commitment, and through equivalents of fulfillment of the commitment such as payment in lieu, transformation of the commitment, representation, execution, and unity of obligation, and other than through fulfillment, release, impossibility of enforcing the commitment and prescription. This research has been conducted with the aim of understanding and recognizing the expiration of commitment in jurisprudence and the Civil Code of Afghanistan. This research is applied in terms of purpose and descriptive-analytical in nature, and the data of this research has been analyzed qualitatively. The findings of this research have shown that there is a correspondence between commitment in jurisprudence and the Civil Code of Afghanistan. The findings of this research can be useful for judges, defense lawyers, and professors of law and political science at universities in Afghanistan.